The late-Holocene tufa decline in Europe: Myth or reality?. (15th February 2020) - Dabkowski, Julie
Abstract: In 1993, Goudie and co-authors named the postulate that there would be a marked decline in the deposition of calcareous tufa in Europe since ca. 2500 BP 'the late-Holocene tufa decline'. However, the growing development of investigation on calcareous tufas and considerable improvement in dating methods, especially radiocarbon dating, has provided reliable evidence of deposits developing until our present days. I thus discuss the reality of the decline, reviewing 62 tufa sites in Europe and their time distribution based both on radiocarbon dates and biochronological data and distinguishing different cases depending on tufa size and types. I demonstrate that the late-Holocene tufa decline is actually a general view of a rather complex tendency: after a maximum during the Atlantic period, fluvial tufas are systematically affected by a decline from ca. 5 ka cal. BP but no general trend is shown in the development of proximal (spring-fed) or lacustrine tufas. This observation is likely to result from the increasing impact of human activity (mainly deforestation) on landscapes, and more specifically on fluvial environments, from the Bronze Age. Highlights: Date frequency is not appropriate to discuss tufa distribution during the Holocene. The late-Holocene tufa decline in Europe systematically affects fluvial tufas only. No systematic decline is observed in proximal (spring) and lacustrine tufas. Fluvial tufa deposits are likely to be more exposed to anthropogenic changes.